Analysis of Learning Enthusiasm Through School Culture in Elementary Schools - Liansari, Vevy; Rahmawati, Ayu; Junia, Lovevita; Aulia, Marisca Putri; Rismawati, Riya (Procedia of Social Sciences and Humanities, 2024)
This study discusses the school culture in elementary schools to increase the enthusiasm for learning, school culture in elementary schools also plays a crucial role in forming a conducive learning environment and supporting student development. This culture includes values, norms, and practices that are upheld by all school members, including students, teachers, and administrative staff. This study aims to identify and analyze the main elements of school culture in elementary schools and their impact on the quality of learning and character development of students. School culture has a very important role in increasing the enthusiasm for learning of students in elementary schools. However, there are still few studies that use experimental methods to examine the influence of school culture on the enthusiasm for learning of students in elementary schools. Therefore, this study aims to examine the influence of school culture on increasing the enthusiasm for learning of students in elementary school.